2018
DOI: 10.1088/1361-6528/aad39b
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework derived cobalt phosphosulfide with ultrahigh microwave absorption properties

Abstract: Nanostructure composites of ferromagnetic materials embedded in nanoporous carbon (NC) derived from metal-organic frameworks (MOFs) have attracted enormous attention due to their potential application in many fields, such as microwave absorption, energy storage, and conversion. The rational design of nanocomposites holds a determinant factor for overcoming the challenges involving the microwave absorption performance. Herein, CoS/NC, CoP/NC, and CoSP/NC with a rhombic dodecahedral structure have been successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 52 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Ferrite, metal particle, carbon, and conductive polymer materials can be used in microwave absorption, but they have some disadvantages such as poor impedance matching and poor absorption performance when used alone. [128][129][130][131] For example, ferromagnetic metals such as iron, cobalt, nickel, and their alloys have strong absorption strength, but their disadvantages such as narrow absorption bandwidth and high density limit their practical applications. In contrast, carbon-based materials such as graphene and carbon nanotubes are excellent light microwave absorption materials.…”
Section: Mofs Derived Carbon-based Magnetic Metal Particle Composite ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrite, metal particle, carbon, and conductive polymer materials can be used in microwave absorption, but they have some disadvantages such as poor impedance matching and poor absorption performance when used alone. [128][129][130][131] For example, ferromagnetic metals such as iron, cobalt, nickel, and their alloys have strong absorption strength, but their disadvantages such as narrow absorption bandwidth and high density limit their practical applications. In contrast, carbon-based materials such as graphene and carbon nanotubes are excellent light microwave absorption materials.…”
Section: Mofs Derived Carbon-based Magnetic Metal Particle Composite ...mentioning
confidence: 99%
“…Some studies have shown that the introduction of nonmetallic heteroatoms (such as nitrogen and boron atoms) into carbon materials can lead to electronic modulation, resulting in improving the microwave shielding performance. [170,171] The work of Ruan et al [129] showed that the phosphating and vulcanization of Co/NC can obviously improve the microwave absorption properties of the composite. They embedded ferromagnetic nanoparticles into NC matrix and successfully prepared CoS 2 / NC (nanoporous carbon), CoP/NC, and CoS 2-x P x /NC with rhombic dodecahedral structure based on Co-MOFs (ZIF-67).…”
Section: Mofs Derived Nonmetal-doped Carbon-based Microwave Absorptio...mentioning
confidence: 99%
“…[1][2][3] Currently, research is being conducted worldwide to develop the technologies of hydrogen production and storage. 4 Numerous hydrogen storage materials have been investigated including metal hydrides, 5 hydrogen storage adsorption materials, 6 organic hydrogen storage materials, 7 and ligand hydrides, 8 among others.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread application of electronic and electrical equipment, wireless communication systems, and radar stealth technology, electromagnetic pollution and radiation problems have become increasingly serious, especially in the GHz band. 1,2 The most effective way to solve these issues is to use highefficiency microwave absorbing materials (MAMs) to absorb the electromagnetic waves and avoid strong electromagnetic wave reection and secondary pollution. 3,4 Hence, a considerable amount of effort has been devoted to the preparation of MAMs with multiple performance requirements.…”
Section: Introductionmentioning
confidence: 99%